Penerapan Model Pembelajaran PIMCA untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik SMA pada Materi Kalor - Diki Aditya; Muslim; Dedi Sasmita (Mataram University, 2026)
Problem-solving skills are one of the most important skills for students to possess; however, their proficiency in this area remains low, necessitating a learning model that actively engages students and fosters a strong conceptual understanding. This study aims to determine the effectiveness of the PIMCA learning model in improving problem-solving skills in heat-related material. A quantitative approach was used with a quasi-experimental design. The sample in this study was determined using convenience sampling, while data on problem-solving skills were collected through tests and analyzed using N-Gain, hypothesis testing in the form of an independent samples t-test, and effect size calculations. The analysis results show that the average N-Gain score for problem-solving skills among students in the experimental class was 0.59, which is higher than that of the control class, which was only 0.43. The results of the independent samples t-test yielded a significance value of < 0.001, indicating a significant difference in the improvement of problem-solving skills. Furthermore, the effect size calculation yielded a value of 1.4, which falls into the high category. Thus, the PIMCA model has a positive impact on students’ problem-solving skills regarding heat-related material. Based on the research results, it can be concluded that the PIMCA model can serve as an alternative instructional model to enhance students’ problem-solving skills.